Tindakan Hukum terhadap Pelaku Lesbian, Gay, Biseksual, dan Transgender di Wilayah Kota Jambi - Hisbah Hisbah; Dedy Syaputra; Yudi Ramadhan (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to determine the legal prohibitions and obstacles faced in prosecuting LGBT perpetrators in Jambi City. This research is an empirical legal research aimed at finding solutions to problems arising within the context of the relevant legal phenomenon. The results of this study conclude that legal prohibitions against LGBT perpetrators in Jambi City remain repressive.